KRITIK SASTRA TERHADAP PERANG SEBAGAI TRADISI DALAM CERPEN AMA TOBI DI ANTARA KONFLIK BATAS KAMPUNG KARYA SILVESTER PETARA HURIT: PENDEKATAN SOSIOLOGI SASTRA DALAM ANALISIS MARXISME - Imelda Oliva Wissang; Carlos Konda Tupen Masan (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2025)
This study aims to describe literary criticism of war as a tradition in the short story Ama Tobi di Antara Pertahanan Batas Kampung by Silvester Petara Hurit - A Sociological Approach to Literature in Marxist Analysis using a descriptive qualitative research method. The results of the study of literary criticism of war as a tradition in the short story Ama Tobi di Antara Kebudayaan Batas Kampung by Silvester Petara Hurit - A Sociological Approach to Literature in Marxist Analysis can be concluded as follows, (1) war was born because of the occupation and economic control of the colonialists. Some traditions that we know today are modern engineering that are packaged as if they came from the past, (2) the attitude of considering war as a tradition is an attitude of Over Proud towards the tradition itself, (3) tradition is a cultural expression that always interacts with new values that show an attitude of respecting human rights, (4) empirically, war that is carried out physically has caused collective trauma, divisions between clans, and revenge that is difficult to break, and (5) the best legacy of tradition is values that strengthen the community such as deliberation, mutual cooperation, respect for ancestors, and peaceful conflict resolution.